Diagnóstico turístico - Ambiental de los sitios turísticos del campus Salache, Universidad Técnica de Cotopaxi. - Valverde Agudo, Oldemar Josué (2021)
This project consists of a tourist-environmental diagnosis of the Salache campus, of the Technical University of Cotopaxi, located in the southwest of the Latacunga canton. For the development of the project, an analysis of the environmental state of the campus has been carried out by means of the Rapid Ecological Assessment, which was carried out through field trips, contrasted with bibliographic information obtained from the study area; The site is an intervened area, which has buildings and access roads of different order, for this reason the file was applied in three different areas, the first in the lower part divided by the main access road to the site where there are new buildings and heritage, with some green areas with introduced species as well as fruit trees and growing areas; The second area has classrooms and laboratories, mainly contrasted with short-cycle cultivation areas, finally in the upper area there is a recreation area with fields as well as vegetation spaces both in the area and intervened. Subsequently, the tourist diagnosis was made, through the use of SWOT, where they were determined according to the characteristics of the site; whose main strength is that it has green spaces suitable for leisure and recreation activities as well as proposing the conservation of the environment; Its main threat was that due to the new variants of COVID-19 there are problems for the access of people, new confinement due to Covid-19 and its new variants, the main opportunity was the recovery of green areas recovered by low traffic from students. and its weakness the little or no dedication and commitment to the project of tourist activation and conservation for the campus. Complementing this process with the analysis of the external and internal components using the MEFE and MEFI matrix, respectively, it was determined that, based on the ratings provided, survival strategies should be proposed. With the aforementioned, a proposal was raised that allows the design of strategies according to the result obtained, where the main one is to take advantage of the environmental condition so that sustainable tourist activities are proposed, which promote the reactivation and visit of the campus for both the students of the faculty. and the university, as well as for the external groups that constantly visit the campus, for academic and research purposes, which are also considered tourist elements.